John Holmes Poetry - 'V' - Holmes, John (Tufts Archival Research Center, 2019)
Page 3 of poetry notebook given to Muriel Simonson by John A. Holmes, circa 1930. (First two are blank.) Poem begins 'There are faces,/People talk.'